1982
DOI: 10.1515/zna-1982-0912
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Shell Structures in an MgCl2 Solution from X-Ray and MD Studies

Abstract: The results of a molecular dynamics simulation of a 1.1 molal aqueous MgCl2 solution are compared with newly performed x-ray measurements. The structural properties of the solution are evaluated from the scattering data by a model fit to the experimental structure function. The comparison on the basis of fit parameters and partial structure functions shows an overall good agreement between experiment and simulation.Detailed information on the structure of the hydration shells is deduced from the simulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 8 publications
5
9
0
Order By: Relevance
“…4,57,58 In contrast, experimental studies 38,44 show no sign of contact ion pairs between magnesium and chloride ions in MgCl 2 solutions; the first peak of the neutron signal ΔG Mg−W (r) can thus be readily assigned to the Mg−O distance. The presently obtained value of 2.05 Å, falls within the range of experimental values, 2.0 to 2.12 Å, previously reported in the literature, [42][43][44]59,60 but is shorter than the most recent neutron scattering estimate 44 of 2.10 Å. The position of the first peak is found here to be rather insensitive to the employed signal treatment.…”
Section: ■ Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…4,57,58 In contrast, experimental studies 38,44 show no sign of contact ion pairs between magnesium and chloride ions in MgCl 2 solutions; the first peak of the neutron signal ΔG Mg−W (r) can thus be readily assigned to the Mg−O distance. The presently obtained value of 2.05 Å, falls within the range of experimental values, 2.0 to 2.12 Å, previously reported in the literature, [42][43][44]59,60 but is shorter than the most recent neutron scattering estimate 44 of 2.10 Å. The position of the first peak is found here to be rather insensitive to the employed signal treatment.…”
Section: ■ Methodssupporting
confidence: 87%
“…We thus need to refine the original full charge force field by scaling the ionic charge and readjusting the ionic radius to obtain a scaled-charge ECC force field with the proper Mg–O distance. In a first ECC model, we tune σ to obtain a 2.10 to 2.12 Å Mg–O distance, following the estimates obtained in previous works, labeling this model as “ECC big”. Figure b shows that this model improves the agreement with neutron scattering compared with a full charge force field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the hydration structure of Mg 2+ is relatively unambiguous. X-Ray Diffraction (XRD), 2,34 Neutron Diffraction (ND), 35 Raman spectroscopy, 36,37 Density Functional Theory (DFT), 38,39 MD 34,36,40 and AIMD [41][42][43][44] investigations all report a coordination number (CN) of 6 with the first shell Mg-O distance is found experimentally to be between 2.10 and 2.12 Å. [35][36][37][45][46][47][48] One gas phase DFT study investigating the successive binding energies of water to Mg 2+ by Pavlov et al 49 found stable structures up to a CN of 7.…”
Section: +mentioning
confidence: 99%
“…The solvation structures of MgCl 2 in aqueous solution have been studied with the help of classical molecular dynamics simulations. The hydration structure of Mg 2+ has been investigated by many first principal molecular dynamics and Monte Carlo simulations. It is observed from studies of solvation structures of magnesium chloride using ab initio molecular dynamics, density functional theory, and Car–Parrinello molecular dynamics (CPMD) that in the first solvation shell of magnesium ion there are six water molecules arranged in an octahedral arrangement around magnesium ion and the radius of first solvation shell ranges from 2.01 to 2.13 Å. …”
Section: Introductionmentioning
confidence: 99%